1991
DOI: 10.1159/000147188
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Os goniale in Man

Abstract: The anterior process of the malleus of the middle ear develops irrespective of Meckel’s cartilage through an intramembranous ossification center that appears in the human embryo of 26.5 mm crown-rump length at a caudo-medial position in relation to Meckel’s cartilage. The malleus has a double origin: the anterior process originates from the os goniale through intramembranous ossification, and the rest from MeckeΓs cartilage through endochondral ossification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Likewise, the degenerating MC might induce the transformation of the AP–goniale complex to provide a fibrous band to add to or replace the usual SML. These transformations appeared to occur in stages between 19 and 26 weeks because we did not find such a strange protrusion in fetuses aged 16–18 weeks (CRL of 125–155 mm) in our previous studies (Rodríguez‐ Vázquez et al., 2020, 1991, 1992, 1993, 2011, 2016, 2018). A clue of the hypothetical transformation of the tympanic ring by the degenerating MC appeared to be found in the specific matrix (Sakakura et al., 2005; Shibata et al., 2014, 2019).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Likewise, the degenerating MC might induce the transformation of the AP–goniale complex to provide a fibrous band to add to or replace the usual SML. These transformations appeared to occur in stages between 19 and 26 weeks because we did not find such a strange protrusion in fetuses aged 16–18 weeks (CRL of 125–155 mm) in our previous studies (Rodríguez‐ Vázquez et al., 2020, 1991, 1992, 1993, 2011, 2016, 2018). A clue of the hypothetical transformation of the tympanic ring by the degenerating MC appeared to be found in the specific matrix (Sakakura et al., 2005; Shibata et al., 2014, 2019).…”
Section: Discussionmentioning
confidence: 47%
“…The present study demonstrated that the AP–goniale complex was sometimes long enough to reach the infratemporal fossa. The membranous bone appears in fetuses at 16–18 weeks (125–155 mm in CRL) (Rodríguez‐Vázquez et al., 1991, 2016), and it does not replace the initial cartilaginous connection between the MC and malleus but “adds or newly builds” just below the initial connection (Figure 1b). Because the AP–goniale complex was continuous with the secondary periosteal bone of the malleus, its color was similar to the periosteal bone collar of a long bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been known that the first reflex movements of mouth opening occur at 8–9 weeks of gestation (Humphrey, 1968), at which time the temporomandibular joint has not yet formed (Mérida‐Velasco et al, 1999). Instead, there is a connection between the dorsal end of Meckel's cartilage (which would give rise to the malleus) and the incus (Rodríguez Vázquez et al, 1991). Therefore, any fetal movements at this stage of development must involve this joint, which would be the primary jaw articulation (Mérida‐Velasco et al, 1990).…”
Section: Discussionmentioning
confidence: 99%